2023
DOI: 10.3389/fenvs.2023.1126565
|View full text |Cite
|
Sign up to set email alerts
|

Can environmental information disclosure reduce air pollution? Evidence from China

Abstract: Previous studies have focused on the reduction effect of regulation-based instruments and economic-based instruments on air pollution, ignoring the importance of environmental information disclosure. Based on the Ambient Air Quality Standards (AAQS), a quasi-natural policy implemented in 2012, this paper assesses the effect of environmental information disclosure on air pollution through a dynamic spatial difference-in-difference (DID) model using panel data of 269 cities from 2006 to 2017 in China. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Public awareness and support are important for environmental policies designed to resolve air pollution issues [52]. Public environmental campaigns to reduce air pollution can take many forms, from government policies to citizen-led initiatives [53]. For example, Environmental tax reform can significantly reduce urban air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Public awareness and support are important for environmental policies designed to resolve air pollution issues [52]. Public environmental campaigns to reduce air pollution can take many forms, from government policies to citizen-led initiatives [53]. For example, Environmental tax reform can significantly reduce urban air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, studying how to encourage GI has become increasingly important across various fields (Hu et al, 2022;Abbas et al, 2023). Furthermore, EID is essential among the many forms of non-governmental environmental regulation (Du L. et al, 2022;Xiong et al, 2023). The EID method has been implemented and improved with the help of digital technology to compensate for the shortcomings of government regulation and market-based incentives.…”
Section: Statistical Variablesmentioning
confidence: 99%
“…Using panel data of prefecture-level cities, Zhang and Feng [27] empirically tested the relationship between environmental information disclosure and urban carbon emissions by constructing a DID model and found a significant negative relationship between them, verifying the effectiveness of environmental information disclosure, and the heterogeneity indicated that its emission reduction effect was more obvious in the east and west regions. Some scholars' studies have also concluded that environmental information disclosure can reduce pollution emissions [28][29][30][31][32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%